Motivasi Kerja dan Lingkungan Kerja Terhadap Kinerja Pegawai Pada PT PLN - Indaryani, Indaryani; Angka, A, Fitri Sugi; Anggerwati, A. Indah (Fakultas Ekonomi dan Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2024)
The objectives of this study were (1) To determine work motivation and work environment partially affect employee performance at PT PLN ULP Mattirotasi Parepare. (2) To determine work motivation and work environment simultaneously affect employee performance at PT PLN ULP Mattirotasi Parepare. Data collection techniques that researchers use in this study are observation, interviews, questionnaires, and documentation. As a population, all employees of PT PLN ULP Mattirotasi Parepare. In order for this research to be precise and proportional, in this study saturated sampling was used where population members were sampled. The number of samples to be studied is 30 people. The results of this study indicate that (1) Work Motivation Variable (X1) has a partial effect on Employee Performance at PT PLN ULP Mattirotasi Parepare with tcount> ttable (-2.031> 2.051) and significant <0.05 (0.052 <0.05). (2) Work Environment Variable (X2) has no partial effect on Employee Performance at PT PLN ULP Mattirotasi Parepare with the results of tcount < ttable (-1.814 > 2.051) and significant > 0.05 (0.081 < 0.05). (3) Work Motivation and Work Environment simultaneously affect Employee Performance at PT PLN ULP Mattirotasi Parepare with Fcount> Ftable (4.160> 3.34) and significant <0.05 (0.027 <0.05). (5) The value of R2 = 0.236 means that the influence of Work Motivation (X1) and Work Environment (X2) variables on Employee Performance (Y) is 23.6%. While the remaining 76.4% is influenced by other variables not included in this study such as leadership style, leadership, job satisfaction, compensation, etc.